Anticoagulant therapy after venous thromboembolism and 10-year mortality. (1st April 2016) - Larsen, Torben Bjerregaard; Lip, Gregory Y.H.; Gorst-Rasmussen, Anders
Abstract: Background: Pulmonary embolism (PE) is associated with a higher long-term mortality than deep vein thrombosis (DVT). This association may be related to inadequate antithrombotic therapy. Methods: Incident VTE patients during the period 1997–2012 were identified in Danish nationwide registries. Two landmark populations were defined, consisting of patients alive at 30 days (30 d), and at 180 days (180 d) after discharge. Patients were classified according to anticoagulant usage at the landmark (30 d: prescription purchase 0–30 d post-discharge; 180 d: prescription purchase in 0–30 d and 90–180 d). Mortality rates were compared using multivariate Cox regression. Results: The 30 d mortality risk among PE patients was high compared to DVT patients (19.9% vs. 4.4%). In the 30 d-landmark population (n = 62695), 34.9% of DVT patients and 21.3% of PE patients had not redeemed a prescription for anticoagulants. There was no material difference in 10-year mortality between anticoagulated PE patients and anticoagulated DVT patients. There was a higher 10-year mortality rate among non-anticoagulated PE patients compared to anticoagulated DVT patients (MRR: 1.26, 95% CI: 1.20–1.33). Findings in the 180 d-landmark population also indicated materially similar 10-year mortality rates between anticoagulated PE patients and anticoagulated DVT patients. Conclusions: The 10-year mortality rate of patients surviving the initial 30 d critical period following incident PE was not increased compared to patients with incident DVT, as long as patients initiated and persisted with anticoagulant therapy. Increased focus on antithrombotic therapy in PE patients and reasons for early therapy discontinuation may be warranted.